CELLULOSE WITH URETHANE CROSS-LINKS DECORATED WITH IONIC FUNCTIONAL GROUP FOR WASTE WATER PURIFICATION FROM TOXIC METAL IONS - Khaseeb, Shorouq (An-Najah National University, 2024)
Background: water is elixir of life. Excessive chemical use in varies sectors, whether in industry, agriculture or other, can result in an increased load of pollutants in water. Radionuclides, household chemicals, pharmaceuticals and personal care products (PPCPs), microorganisms, plumbing inorganic chemicals, and other contaminants are common in water. Heavy metals are among the most harmful of these pollutants owing to their lasting effects, and toxicity even at low concentration. As a result, removing these hazardous heavy metal ions from water is becoming crucial. Objectives: The purpose of this thesis is to establish novel adsorbent material based on polyurethane foam (PUF) that was enhanced with an ionic functional group capable of efficiently absorbing harmful metals from water. Methodology: The process of creating the target polymers included a series of chemical reactions between carboxymethyl cellulose (CMC) and diisocyanate compounds (hexamethylene diisocyanate & phenylene diisocyanate) in the presence of diisopropyl amine as a catalyst, resulting in the formation of the foam polymeric materials carboxymethyl cellulose hexamethylene polyurethane foam (CMC-HMPUF) and carboxymethyl cellulose phenylene diisocyanate polyurethane foam (CMC-PPUF) with urethane links. Results: The adsorption capacity of polymeric foams toward Pb(II) was assessed using a variety of parameters such as temperature, pH, adsorbent dose, time and initial ion concentration. In addition, the optimal value of each of the parameters that resulted in quantitative elimination of Pb(II) were discovered. The percentage removal of Pb(II) by CMC-HMPUF polymer was around 95%, while CMC-PPUF was approximately 93%. Adsorption thermodynamics, kinetics, and isotherms were also studied to gain insight into the mechanism and spontaneity of adsorption. The result demonstrate that the adsorption of Pb(II) process is classified exothermic process (∆H°<0), and spontaneous at low temperatures (∆G°<0),( ∆S°<0). The obtained isothermal and kinetic values illustrated that the adsorption by the two foams fit the Freundlich model, and obey a Pseudo-second order kinetic. The created foams exhibited a great propensity to remove multi-metal ions found in an actual sample of sewage water. Conclusion: The goal polymers were made, and urethane linkages were detected using IR spectroscopy, the two polymers foam showed strong thermal stability, they were effective in removing heavy metals from wastewater.
سيليلوز مع روابط عرضية من اليوريثان مزينة بمجموعة وظيفية أيونية لتنقية مياه الصرف من أيونات المعادن السامة